Presumptive mood, factivity and epistemic indefinites in Romanian - Falaus, Anamaria (Borealis – An International Journal of Hispanic Linguistics, 2014)
This paper investigates the properties of the Romanian presumptive mood and the role it plays in the distribution of the epistemic indefinite vreun. We focus on the morphologically complex future-based paradigm, which includes forms based on the literary and colloquial variants of the future auxiliary. The colloquial forms are shown to have lost the ability to express purely temporal meanings, being used exclusively with modal-evidential readings. We further argue that the future-based presumptive is closely related to epistemic modals, with which it shares the ability to express indirect inferential evidentiality. We capitalize on their contrasting behavior in factive settings to explain the interaction with the epistemic determiner vreun. Specifically, we argue that the key property that makes the (colloquial) future-based presumptive a suitable licensor for the vreun is its incompatibility with contexts where the modalized proposition is established to hold.